Genetic doping: realities, perspectives of application in sports and bioethical aspects - Gorchakova, N.; Belenichev, I. F.; Hnatiuk, V.; Oliynyk, S.; Kuchkovskyi, O. M.; Moshkivska, J.; Doroshenko, E. Yu.; Горчакова, Н.; Бєленічев, Ігор Федорович; Гнатюк, В.; Олійник С.; Кучковський, Олег Миколайович; et al. (My University, 2023)
The authors of the article, based on their own research, as well as taking into account the numerical results of other scientists, set out modern ideas about the use of gene doping in sports. In recent years, significant progress has been made in the use of gene therapy for the treatment of patients. However, some new substances can be used as gene doping in athletes. This provides greater physical endurance, the rapid growth of muscle mass, etc. It has been proven that such manipulations of genetic material and/or the introduction of recombinant proteins may be associated with health risks. In particular, great concern is caused by the potential impact of these substances on the human cardiovascular system, which can lead to catastrophic consequences, such as myocardial infarction. New developments by scientists have led to the appearance of tools, which directly affect the key links of success in sports – energy supply mechanisms and the quality and duration of effective muscle contraction. A potential benefit of genetic modification in sports is the elimination or significant reduction of gender discrimination in sports. Although discrimination is likely to be an ongoing ethical problem, it is interesting that genetic manipulation may be a step toward finding a solution. The main argument in favor of genetic technology and its potential impact on gender discrimination in sports is that people whose genes are designed for athletic advantage can compete and be judged solely on athletic performance, thereby making gender a non-factor. Although research is currently limited and inconclusive, there is a tentative consensus that genetically modified athletes will have some advantage over non-genetically engineered athletes. In elite sports, this advantage, even if it is very small, can be decisive in close competition. Medical specialists from the WADA Anti-Doping Commission consider it their duty to warn athletes, coaches, and doctors about the serious danger associated with taking these substances. Don’t let anyone be fooled by frivolous advertising and artificial hype surrounding these doping. They are deadly. Don’t let anyone be fooled by frivolous advertising and artificial hype surrounding these doping. They are deadly. Don’t let anyone be fooled by frivolous advertising and artificial hype surrounding these doping. They are deadly. Aim. The purpose of this study is to provide an up-to-date semantic analysis of our own results and literature data on the biomedical and bioethical aspects of genetic doping and the prospects for its use in sports. Автори статті на підставі власних досліджень, а також з огляду на численні результати інших науковців виклали сучасні уявлення про використання генетичного допінгу у спорті. Останніми роками було досягнуто значного прогресу у використанні генної терапії для лікування хворих. Однак деякі нові речовини можуть використовуватись як генний допінг у спортсменів. Це надає більшої фізичної витривалості, швидкого зростання м’язової маси тощо. Доведено, що подібні маніпуляції з генетичним матеріалом та/або введення рекомбінантних білків можуть бути пов’язані з ризиком для здоров’я. Зокрема, велике занепокоєння викликає потенційний вплив цих речовин на серцево-судинну систему людини, що може призвести до катастрофічних наслідків, таких як інфаркт міокарда. Нові розробки вчених призвели до появи засобів, які безпосередньо впливають на ключові ланки успіху у спорті – механізми енергозабезпечення та якість і тривалість ефективного м’язового скорочення. Потенційною перевагою генетичної модифікації у спорті є усунення чи значне зниження ґендерної дискримінації у спорті. Хоча дискримінація, найімовірніше, буде постійною етичною проблемою, цікаво, що генетичні маніпуляції можуть стати кроком до пошуку рішення. Головний аргумент на користь генетичних технологій та їхнього потенційного впливу на дискримінацію за ознакою статі у спорті полягає в тому, що люди, чиї гени створені для спортивної переваги, можуть змагатися та оцінюватись лише за спортивними результатами, тим самим роблячи ґендер не фактором. Хоча дослідження нині обмежені та непереконливі, є попередній консенсус щодо того, що генетично модифіковані спортсмени матимуть певну перевагу перед тими, хто не є продуктом генетичних технологій. В елітному спорті ця перевага, навіть якщо вона дуже маленька, може мати вирішальне значення в тісному змаганні. Фахівці-медики з Антидопінгової комісії ВАДА вважають за свій обов’язок попередити спортсменів, тренерів, лікарів про серйозну небезпеку, пов’язану з прийманням цих речовин. Нехай нікого не обманює легковажна реклама та штучний ажіотаж навколо цих допінгів. Вони смертельно небезпечні. Мета дослідження полягає в тому, щоб зробити актуальний семантичний аналіз власних результатів та даних літератури з медико-біологічних та біоетичних аспектів генетичного допінгу та перспектив його використання у спорті.
Генетичний допінг: реалії, перспективи застосування у спорті та біоетичні аспекти
Бєленічев І. Ф. - ORCID: 0000-0003-1273-5314; Кучковський О. М. - ORCID: 0000-0002-0548-0029; Дорошенко Е. Ю. - ORCID: 0000-0001-7642-531X
Keywords: sports pharmacology; genetic doping; types of gene modifications; pharmacological agents; pharmacological targets; bioethics; спортивна фармакологія; генетичний допінг; типи генних модифікацій; фармакологічні агенти; фармакологічні мішені; біоетика